Cost-utility Analysis of Neoadjuvant Teriparatide Therapy in Osteopenic Patients Undergoing Adult Spinal Deformity Surgery. Issue 16 (15th August 2022) - Raad, Micheal; Ortiz-Babilonia, Carlos; Hassanzadeh, Hamid; Puvanesarajah, Varun; Kebaish, Khaled; Jain, Amit
Abstract : Study Design: A cost-utility analysis study. Objective: This study aims to evaluate the cost-utility of neoadjuvant teriparatide therapy in osteopenic patients undergoing adult spinal deformity (ASD) surgery. Summary of Background Data: There is increasing evidence supporting preoperative use of anabolic agents such as teriparatide for preoperative optimization of ASD patients with poor bone density. However, such treatments are associated with added costs. To our knowledge, the cost-utility of teriparatide in osteopenic patients undergoing ASD surgery has not been established. Materials and Methods: A decision-analysis model was developed for a hypothetical 68-year-old female patient with osteopenia ( T score <−1.0) undergoing a T11 to pelvis instrumented spinal fusion for ASD. A comprehensive literature review was conducted to create estimates for event probabilities, costs, and quality adjusted life years at each node. Key model assumptions were that administration of a 4-month preoperative teriparatide course reduced 2-year postoperative reoperation rates [for pseudarthrosis from 5% to 2.5% and for proximal junctional failure (PJF) from 15% to 5%]. Monte Carlo simulations were used to calculate the mean incremental cost utility ratio and incremental net monetary benefits. One-way sensitivity analysis was used to estimate the contribution of individual parameters to uncertainty in the model. Results: Teriparatide was the favored strategy in 82% of the iterations. The mean incremental cost utility ratio for the teriparatide strategy was negative (higher net benefit, lower net cost), and lower than the willingness-to-pay threshold of 50, 000 per quality adjusted life year. Teriparatide use was associated with a mean incremental net monetary benefit of 3, 948. One-way sensitivity analysis demonstrated that the factors with the greatest impact on the model were the incidence of PJF in the no teriparatide group, the duration and monthly cost of treatment, and the cost of reoperation due to PJF. Conclusions: Neoadjuvant teriparatide is a cost-effective strategy to reduce postoperative complications in patients with osteopenia undergoing ASD surgery.